The anti-depressive role of the Pei Yuan Kai Yu formula in cerebral small vessel disease based on gut microbiota - Yang, Lixuan; Ao, Yutian; Li, Yannan; Dai, Baoan; Li, Junnan; Duan, Wenzhe; Dong, Kaiqiang; Han, Zhenyun; Guo, Rongjuan (Frontiers in Pharmacology, 2025)
BackgroundCerebral small vessel disease (CSVD), characterized by pathological changes in brain vessels, is a common cause of death in the elderly and often accompanied by depression, which significantly affects patients’ quality of life and rehabilitation; understanding its pathogenesis and developing innovative therapies are urgently needed, especially considering the role of the blood - brain barrier impairment and the gut - microbiota - gut - brain axis in this complex condition.MethodsDahl/SS rats were fed a diet containing 8% NaCl and were subjected to chronic unpredictable mild stress (CUMS) stimulation for 4 weeks. PY (1.407 g/kg/day) was administered intragastrically to evaluate its role in CSVD with depression. Pseudo germ-free rats were colonized with gut microbiota from high-salt-fed rats exposed to CUMS, followed by PY administration.ResultsIn rats with CSVD and depression, PY significantly increased body weight; alleviated depression-like behaviors; and decreased the levels of inflammatory cytokines such as TNF-α, IL-1β, and IL-6 in both serum and hippocampus. Additionally, PY reversed inflammation-induced nerve damage; reduced the overexpression of microglia in the hippocampus; decreased the levels of hippocampal VEGF and MMP-9, and increased the levels of hippocampal occludin, ZO-1, and claudin-5. Moreover, PY improved the composition of gut microbiota and enhanced microbial diversity. PY induced characteristic changes in the microbiome, which were associated with inflammation, endothelial dysfunction, and depressive-like behaviors. These significant metabolites were identified and were found closely related to inflammation, endothelial cell dysfunction, and depression-like behaviors.ConclusionIn conclusion, PY acts as an antidepressant to slow down the progression of CSVD by inhibiting microglial activation, reducing inflammation and ameliorating endothelial dysfunction. It exerts its effect, at least in part, by enhancing microbiota-mediated metabolism in vivo.